1977
DOI: 10.1007/bf02912384
|View full text |Cite
|
Sign up to set email alerts
|

Peanut protein: A versatile food ingredient

Abstract: Peanut flour has been evaluated for use in a variety of food products as a replacement for animal source proteins. In breakfast cereals and snack foods, peanut flour blends well with cereal flours to yield products with excellent flavor, texture, and color. Peanut flour can be used to produce textured vegetable protein or can be used directly in ground meats to provide good moisture and fat binding characteristics. In bakery products, peanut flour can be used at levels up to 20% to provide protein supplementat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1981
1981
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Several studies of beef patties extended with soy or peanut protein ingredients also showed a beneficial effect for yield by the oilseed proteins (Anderson and Lind, 1975;Ayres and Davenport, 1977;Bowers and Engler, 1975;Drake et al, 1975;McWatters, 1977;Smith et al, 1976). With patties cooked from the frozen state, however, Thomas et al (1978) found a higher yield for all-beef patties than for beef-soy (textured) patties.…”
Section: Yieldmentioning
confidence: 99%
“…Several studies of beef patties extended with soy or peanut protein ingredients also showed a beneficial effect for yield by the oilseed proteins (Anderson and Lind, 1975;Ayres and Davenport, 1977;Bowers and Engler, 1975;Drake et al, 1975;McWatters, 1977;Smith et al, 1976). With patties cooked from the frozen state, however, Thomas et al (1978) found a higher yield for all-beef patties than for beef-soy (textured) patties.…”
Section: Yieldmentioning
confidence: 99%
“…Ayres and Davenport (1977) extruded corn, oat, and defatted peanut flour mixtures to produce breakfast cereals. Aguilera et al(1980) extruded defatted peanut flour to produce fibrous, meat-like extrudates.…”
Section: Introductionmentioning
confidence: 99%
“…Peanut is a good source of supplementary protein and is used to produce widely accepted food products (Matz, 1993), and peanut flour may be added as an ingredient in extrusion products. Ayres and Davenport (1977) extruded corn, oat, and defatted peanut flour mixtures to produce breakfast cereals. Aguilera et al(1980) extruded defatted peanut flour to produce fibrous, meat-like extrudates.…”
Section: Introductionmentioning
confidence: 99%
“…Extrusion of mixtures of brown rice grits and defatted peanut flour gave products with desirable cereal-like flavour and higher protein content (Spadaro et al, 1971). Mixtures of peanut flour and other oilseed flours produced extrudates with high expansion but low structural integrity upon rehydration (Ayres et al, 1974;Ayres & Davenport, 1977), and peanut flour and soy flour mixtures produced more acceptable products. Extrudates with good texture, colour, and appearance were produced from the blends of defatted peanut flour, cornstarch, and gram flour (Bongirwar etal., 1979).…”
Section: Introductionmentioning
confidence: 99%